1980
DOI: 10.1007/bf00122402
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal studies in three species of the genus dacus (Trypetidae: Diptera)

Abstract: Somatic chromosomes and Giemsa C-banding patterns of three species of fruit flies belonging to the genus Dacus, viz., D. cucurbitae, D. zonatus and D. diversus are described. There are five pairs of long, euchromatic autosomes and one pair of smaller sex chromosomes which are homomorphic in females (XX) and heteromorphic in males (XY). In all the species the Y chromosome is in the form of a dot while the X chromosome varies in morphology. The autosomes of D. cucurbitae and D. zonatus are characterized by dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
2
8
1
Order By: Relevance
“…Our findings are much closer to those of Bhatnagar et al (1980) than to those of Gopalan (1972). A slight difference in the interpretation of metacentric and submetacentric chromosomes exists which may be due to technical variations, because Bhatnagar et al (1980) used the squash method.…”
Section: Observations and Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…Our findings are much closer to those of Bhatnagar et al (1980) than to those of Gopalan (1972). A slight difference in the interpretation of metacentric and submetacentric chromosomes exists which may be due to technical variations, because Bhatnagar et al (1980) used the squash method.…”
Section: Observations and Discussionmentioning
confidence: 42%
“…For instance, the karyotype reported by Gopalan (t972) consists of three pairs of metacentric and two pairs of acrocentric autosomes and a slightly heteromorphic acrocentric pair represcnting the sex chromosomes, while Bhatnagar et al (1980) reported again a different karyotype for this species, with one pair of submetacentric and five pairs of metacentric chromosomes including the X chromosomes, the Y being dot-like in the male (Fig. 2).…”
Section: Observations and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is to our knowledge the first contribution to cytogenetics of the genus Dacus, as it is defined today. Previous chromosomal descriptions of Dacus species are referred to D. oleae (Gmelin), D. cucurbitae, D. zonatus and D. diversus (Krimbas 1963;Gopalan 1972;Bhatnagar et al 1980;Singh and Gupta 1984;Mavragani-Tsipidou et al 1992), which were recently assigned to the genus Bactrocera (Drew 1989). D. ciliatus has the same number of chromosomes (2n = 12) found in the mitotic metaphase complement of most tephritids (Fig.…”
Section: Discussionmentioning
confidence: 98%